ZnAl-LDH / TiO2 compound photo-anode material and preparation and application thereof
By using ZnAl-LDH/TiO2 composite photoanode material in the photoelectrochemical cathode protection system, the problems of low light utilization and poor stability of TiO2 photoanode are solved, and the effect of providing long-term cathode protection in NaCl solution is achieved.
Patent Information
- Application Number
- CN202411700131.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing photoelectrochemical cathode protection system, TiO2 as a photoanode has problems such as low light utilization, strong dependence on hole trapping agents, and poor stability in NaCl solution, which limits its application in oceanic environments.
The ZnAl-LDH/TiO2 composite photoanode material was used to construct a TiO2 nanotube array by anodizing method, and nanoflower-shaped ZnAl-LDH was grown on its surface by hydrothermal method to form a composite photoanode material.
Improves the absorption capacity of the composite to visible light, forms a type II heterojunction, improves the separation efficiency of photogenerated carriers, and provides stable cathode protection for up to 12 hours in the NaCl solution without hole trapping agent. .
Smart Images

Figure CN119465165A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photoelectrochemical cathode protection, and in particular relates to a ZnAl-LDH / TiO 2 Composite photoanode materials (ZnAl layered double hydroxide modified titanium dioxide nanotube array composite photoanode (ZnAl-LDH / TiO 2 )) and its preparation and application. Background Art
[0002] Highly fluid, high-salt, and high-oxygen seawater can cause corrosion to metal equipment and cause huge economic losses. Therefore, how to prevent the corrosion of metal equipment in the marine environment is a huge challenge facing corrosion engineers. The corrosion and protection of metals first involves selecting suitable materials or improving the material structure. Secondly, the current corrosion and protection technologies mainly include protective layers, surface treatment technologies, corrosion inhibitors, and electrochemical protection. Among them, electrochemical protection is an important anti-corrosion method. Electrochemical protection is mainly cathodic protection. In the sacrificial anode protection system, there are disadvantages such as the short service life of the anode material and the limited cathodic protection current provided; a large amount of additional electrical energy needs to be continuously input, and the power supply equipment needs to be regularly inspected and maintained, which is time-consuming and labor-intensive, limiting its widespread application in the offshore environment.
[0003] The core of photoelectrochemical cathodic protection technology is the semiconductor that plays the role of photoelectric conversion center. Its unique physical properties are attributed to its energy band structure. When excited by light, the electrons in the valence band (VB) of the semiconductor jump to the conduction band (CB), leaving holes in the valence band. When the semiconductor is connected to the metal through an external circuit, the electrons in the CB are transferred to the surface of the protected metal through the external circuit due to the potential difference, causing the metal potential to shift negatively and be in a thermodynamically stable state, while the holes are also consumed by oxidizing the substances in the corrosive medium, thereby protecting the metal from corrosion. In this process, there is no consumption of semiconductor materials and no environmental problems.
[0004] Titanium dioxide (TiO 2 ) has the advantages of low toxicity, simple preparation method and high stability. It is widely used in the field of photocatalysis and can be used as a stable substrate material in the PEC cathode protection system. 2 When the film is formed, the electrons generated in the valence band are transferred to the conduction band, and at the same time, the 2 Driven by the potential difference with the metal, it transfers to the protected metal surface, making the metal in a thermodynamically stable zone and protecting the metal from corrosion or slowing down the corrosion rate. 2 The band gap is wide (3.2eV), which makes it have low utilization rate of visible light and can only absorb ultraviolet light. At the same time, photogenerated carriers are easy to recombine, which reduces the number of electrons transferred to the metal surface. Therefore, it is necessary to 2The modification is carried out so that it can be widely used in PEC cathodic protection systems.
[0005] TiO 2 The modification of base photoelectrodes includes methods such as morphology evolution, doping, sensitization, enhanced conductivity, and heterojunction construction.
[0006] By adjusting the concentration of reactants, time, pH and other preparation methods and conditions, TiO 2 It has different morphologies, common morphologies include nanoparticles, nanorods, nanotubes, etc. Among them, TiO 2 Nanotube arrays have attracted increasing attention in the preparation of efficient photoelectrodes.
[0007] Doping is done by adding TiO 2 Doping metal and non-metal ions into the lattice changes its lattice structure to increase the TiO 2 Some metal ions can replace TiO by doping 2 Ti in the lattice 4+ The position of TiO 2 The bandgap width of TiO2 is reduced and the light absorption range is widened. Common metal doping includes transition metals such as Fe, Ni, and Co. At the same time, precious metals such as Au, Ag, and Pt are also added to TiO2. 2 Widely used in doping, non-metal doped TiO 2 Mainly refers to replacing TiO with non-metallic elements 2 The O in.
[0008] In addition to the widely used doping strategy, semiconductor sensitization is also a modification method with broad application prospects. Introducing highly conductive networks (carbon materials, conductive polymers, metal oxides) to promote electron transfer ability is considered to be an effective strategy.
[0009] The electron-hole recombination is TiO 2 The main reason for the poor cathodic protection performance of PEC. Heterojunction engineering uses the band gap matching between different semiconductors to enable photoelectrons and holes to be transferred in an orderly manner between different semiconductors, thereby achieving efficient separation of electrons and holes.
[0010] However, considering that most reported TiO 2 The immunity of the base semiconductor to photocorrosion is low, TiO 2 The long-term PEC cathodic protection performance of the photoanode can only be achieved in the presence of hole scavengers (such as Na 2 S and Na 2 SO 3 ) is maintained in the presence of. However, it is unrealistic to use a large amount of hole trapping agents in real seawater. 2The low immunity of the semiconductor to photocorrosion greatly limits the practical application of PEC cathode protection. Therefore, the present invention designs and synthesizes a photoanode material that is free from photocorrosion in the absence of a hole trap based on the practical application of PEC cathode protection. Summary of the invention
[0011] The purpose of the present invention is to solve the problem of using a single TiO 2 As a photoanode for preventing 304SS corrosion, it has low light utilization, strong dependence on hole trapping agents, and poor stability in NaCl solution. A ZnAl-LDH / TiO 2 Composite photoanode materials (ZnAl layered double hydroxide modified titanium dioxide nanotube array composite photoanode (ZnAl-LDH / TiO 2 )) and its preparation and application.
[0012] In order to solve the above problems, the present invention adopts the following technical solutions:
[0013] A ZnAl-LDH / TiO 2 Preparation method of composite photoanode material, constructing TiO by anodic oxidation 2 Nanotube arrays were prepared, and then nanoflower-like ZnAl-LDH was grown on the surface by a hydrothermal method to obtain ZnAl-LDH / TiO 2 Composite photoanode materials.
[0014] TiO 2 The nanotube array was placed in a Zn(NO 3 ) 2 6H 2 O、Al(NO 3 ) 2 9H 2 O, urea and sodium hydroxide solution, and a nanoflower-like ZnAl-LDH was grown on its surface by a hydrothermal method to obtain ZnAl-LDH / TiO 2 Composite photoanode materials.
[0015] The Zn(NO 3 ) 2 6H 2 O、Al(NO 3 ) 2 9H 2 O, urea and sodium hydroxide solution is 0.0675 mol Zn(NO 3 ) 2 6H 2 O, 0.0225 mol Al(NO 3 ) 2 9H2 O and 0.28 mol urea.
[0016] The hydrothermal reaction temperature is 120° C. and the reaction time is 8 h. After the hydrothermal reaction, the material is dried at 60° C. for 12 h to obtain the material.
[0017] The TiO 2 The nanotube array is obtained by anodizing the pre-treated titanium foil to obtain a surface-coated TiO 2 The titanium sheet with the nanotube array is then taken out for use after annealing in a muffle furnace.
[0018] The anodic oxidation was carried out in an electrolyte with a constant DC voltage of 20 V and an oxidation time of 1.5 h at 5 °C min in air. -1 The heating rate was annealed at 450 °C for 2 h.
[0019] The electrolyte is prepared by adding 5.0 g of ammonium fluoride per liter of solution, wherein the solvent is a mixture of ethylene glycol and water in a volume ratio of 10:1.
[0020] A ZnAl-LDH / TiO prepared by the method 2 Composite photoanode material, prepared by the method, the regular nanoflower-like structure is evenly distributed on the surface of the nanotube array ZnAl-LDH / TiO 2 Composite photoanode materials.
[0021] A ZnAl-LDH / TiO 2 Application of composite photoanode materials, the ZnAl-LDH / TiO 2 The application of composite photoanode materials as photoanodes in photoelectrochemical cathodic protection.
[0022] The ZnAl-LDH / TiO 2 Application of composite photoanode materials in inhibiting metal corrosion in photoelectrochemical cathodic protection.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] The present invention uses a simple hydrothermal method to prepare TiO 2 The ZnAl-LDH was deposited by NTAs. The test results showed that the narrow band gap of ZnAl-LDH enhanced the absorption of visible light by the composite and combined with TiO 2 A type II heterojunction is formed to improve the separation efficiency of photogenerated carriers. In addition, due to the stable structure of ZnAl-LDH, it can provide cathodic protection for stainless steel for up to 12 hours in NaCl solution without hole traps, and the stability of the composite material is greatly improved, which has good anti-corrosion properties for stainless steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The TiO 2 SEM images;
[0026] Figure 2 The ZnAl-LDH / TiO 2 SEM image of composite photoanode;
[0027] Figure 3 The ZnAl-LDH / TiO 2 Distribution diagram of Ti, O, Zn, and Al elements in the composite photoanode;
[0028] Figure 4 The ZnAl-LDH / TiO 2 XPS images of the composite (a) full spectrum, (b) Ti 2p, (c) O 1s, (d) Zn 2p and (e) Al 2p fine spectra;
[0029] Figure 5 The ZnAl-LDH / TiO 2 UV-Vis diffuse reflectance visible spectrum of the composite;
[0030] Figure 6 The 304SS and TiO 2 and ZnAl-LDH / TiO 2 Photoinduced iV curve of the complex coupled under intermittent illumination;
[0031] Figure 7 The 304SS and TiO 2 and ZnAl-LDH / TiO 2 OCP curve of the composite coupling under intermittent illumination;
[0032] Figure 8 The 304SS and TiO 2 and ZnAl-LDH / TiO 2 it curve of the complex coupling under intermittent illumination;
[0033] Fig. 9 The 304SS and ZnAl-LDH / TiO 2 Long-term OCP changes of complex coupling;
[0034] Fig.10The ZnAl-LDH / TiO 2 Schematic diagram of the photoelectrochemical cathodic protection mechanism of the composite photoanode under light conditions. DETAILED DESCRIPTION
[0035] The following examples are used to illustrate the present invention, but they are not intended to limit the present invention.
[0036] The present invention adopts an anodic oxidation method to grow TiO on the surface of Ti foil. 2 Nanotube arrays were prepared and nanoflower-like ZnAl-LDH was deposited on TiO 2 Nanotube array surface, thereby obtaining ZnAl-LDH / TiO 2 Nanocomposite photoanode materials.
[0037] The present invention constructs TiO by anodization method 2 Nanotube arrays are then grown on the surface of nanoflower-like ZnAl-LDH by a simple hydrothermal method. The advantages of ZnAl-LDH such as narrow band gap, simple synthesis method and stable structure are utilized to make it compatible with TiO 2 Nanotube array coupling. Not only does the narrow band gap of ZnAl-LDH improve the absorption capacity of visible light, but ZnAl-LDH and TiO 2 NTAs energy band matching, forming type II to improve the efficiency of photogenerated carrier separation, and using the stable structure of ZnAl-LDH, the cathodic protection performance of 304SS under light conditions is improved, the electrode potential of 304SS is reduced, and the corrosion rate of the metal is reduced. It still has long-term and stable cathodic protection performance for 304SS in NaCl solution without hole traps.
[0038] Example 1
[0039] ZnAl-LDH / TiO 2 The preparation process of the photoanode includes the following steps:
[0040] Pretreatment of titanium foil: Ti foil (40 mm × 10 mm × 1 mm) was immersed in deionized water and ethanol for ultrasonic cleaning for 15 min, and then placed in a 4 F(4.5g),H 2 O (25.0 mL), H 2 O 2 (30wt%, 60.0mL), HNO 3 The Ti foil was etched in a solution of 68 wt %, 60.0 mL to remove the oxide on the surface of the Ti foil. After the etching was completed, the surface residual substances were removed by washing with deionized water and ethanol.
[0041] TiO 2 Preparation of nanotube arrays: TiO was grown on the surface of pretreated Ti foil by anodization. 2 The anodizing electrolyte solution consisted of 80.0 mL ethylene glycol, 0.45 g NH 4 F and 8.0 mL of deionized water. The electrolytic cell consists of a two-electrode system with titanium foil as the working electrode and platinum foil as the counter electrode. A constant DC voltage of 20 V was then applied between the two electrodes for 1.5 h, and the electrolyte remaining on the surface was removed by multiple rinses with deionized water and ethanol. After the oxidation process was completed, the electrolyte was heated in air at 5 °C min -1 The TiO 2 Nanotube arrays (see Figure 1 ).
[0042] ZnAl-LDH / TiO 2 Preparation of nanocomposite photoanode: ZnAl-LDH was deposited on TiO by a simple hydrothermal method. 2 NTAs to synthesize ZnAl-LDH / TiO 2 Composite photoanode. The TiO prepared in the above process 2 The nanotube array was placed in a solution containing 3.375 mmol Zn(NO 3 ) 2 6H 2 O, 1.125mmol Al(NO 3 ) 2 9H 2 O, 14mmol urea in 50mL aqueous solution, and reacted in a reactor at 120℃ for 8h. After taking out the sample, it was rinsed with deionized water and ethanol several times to remove the residual solution on the surface, and the sample was dried at 60℃ for 12h to obtain ZnAl-LDH modified TiO 2 Nanocomposite photoanode (ZnAl-LDH / TiO 2 ).
[0043] The above-mentioned ZnAl-LDH / TiO 2 The morphology of the nanocomposite photoanode was characterized by using a Hitachi SU8220 field emission scanning electron microscope (SEM) to detect the morphology of the synthesized composite material (see Figure 2 ).
[0044] The above-mentioned ZnAl-LDH / TiO 2Chemical composition characterization of nanocomposite photoanode: X-ray photoelectron spectroscopy was performed using the American ThermoScientific Escalab 250Xi, with Al Kα x-ray as the incident beam and the C1s peak of 284.8 eV as the standard peak to study the chemical composition of the synthesized material (see Figure 3 and 4 ).
[0045] The above-mentioned ZnAl-LDH / TiO 2 Light absorption performance test of nanocomposite photoanode: The UV-visible diffuse reflectance spectrum of the sample was characterized by using a Japanese Hitachi DRS U3900 diffuse reflectance UV-visible spectrophotometer (DRS) with a wavelength range of 200 to 800 nm (see Figure 5 ).
[0046] The ZnAl-LDH / TiO prepared above 2 The nanocomposite is used as a photoanode to protect 304SS in NaCl solution without hole trapping agent to improve the corrosion resistance of 304SS in NaCl solution (see Figure 6-10 ).
[0047] ZnAl-LDH / TiO 2 Electrochemical performance test of nanocomposite photoanode:
[0048] Electrochemical measurements were performed using a CHI 760E electrochemical workstation. The light source was a 300W xenon lamp with an AM 1.5G filter. The light energy density was 100mW cm -2 The electrochemical tests were all carried out in 3.5wt% NaCl solution to simulate the seawater environment.
[0049] Open circuit potential (OCP) and photocurrent density (it) test: The open circuit potential of the composite photoanode was measured under intermittent visible light. The composite photoanode and 304SS were connected in series as the working electrode (WE), and the saturated calomel electrode (SCE) was used as the reference electrode (RE). The composite material was irradiated with visible light provided by a xenon lamp for 200 seconds at intervals of 100 seconds. In the photocurrent density test, the composite electrode was connected to the working electrode through a copper wire, and the 304SS was connected to the ground wire. The nanocomposite photoanode was irradiated with a visible light source provided by a xenon lamp, once every 100 seconds, and each irradiation was 200 seconds.
[0050] The following results are used to illustrate the effects of the present invention:
[0051] Figure 1 It is TiO 2 The results of SEM testing of the nanotube arrays show that TiO 2The film consists of tightly packed arrays of nanotubes with an average diameter of about 30-50nm.
[0052] Figure 2 It is ZnAl-LDH / TiO 2 The results of SEM test of the composites show that the ZnAl-LDH / TiO 2 In the composite, ZnAl-LDH is evenly distributed on the surface of the nanotube array in a regular nanoflower-like structure, and TiO 2 The surface is well covered.
[0053] Figure 3 ZnAl-LDH / TiO 2 Composite EDS spectrum. It can be seen that ZnAl-LDH / TiO 2 The main elements in the composite are Ti, O, Zn and Al.
[0054] Figure 4 It is TiO 2 Nanotube arrays and ZnAl-LDH / TiO 2 The results of XPS test on the composite. Figure 4 (a) ZnAl-LDH / TiO 2 The peaks of Ti 2p, O1s, C 1s, Zn 2p and Zn 2p were observed in the full spectrum of the composite material. Figure 4 b), TiO 2 and ZnAl-LDH / TiO 2 The difference between the 2p doublet peaks of the complex is 5.7 eV, which is attributed to the Ti in TiO2 4+ In TiO 2 In the O1s spectrum ( Figure 4 c), the two peaks with binding energies of 531.41 eV and 529.99 eV are attributed to the adsorbed hydroxide (-OH) and lattice oxygen (O lat ). ZnAl-LDH and ZnAl-LDH / TiO 2 The deconvolution of the O1s spectrum of the complex shows the adsorbed hydroxide (-OH, 531.32-531.62 eV) and adsorbed water ((H 2 O) ads ,532.38~532.60eV). In addition, ZnAl-LDH / TiO 2 The O1s spectrum of the composite also shows the presence of a small amount of lattice oxygen (530.55 eV), which may be due to the ZnAl-LDH / TiO 2 The content is high, making it possible to detect TiO 2 The content is relatively low.2 middle( Figure 4 d), the peaks observed at 1021.69eV and 1044.71eV are attributed to 2p3 / 2 and 2p1 / 2 in Zn 2p. The peaks observed at 74.19eV and 74.11eV in Al 2p confirm that Al 3+ existence.
[0055] Figure 5 It is TiO 2 Nanotube arrays and ZnAl-LDH / TiO 2 The results of UV-Vis test on the composites show that TiO 2 It mainly absorbs ultraviolet light, and its light absorption threshold is about 380nm. 2 Compared with ZnAl-LDH / TiO 2 The composite material is due to the ZnAl-LDH on TiO 2 With the increase of the surface loading, the light absorption edge is red-shifted, resulting in stronger absorption in the visible light region.
[0056] Figure 6 TiO 2 Nanotube arrays and ZnAl-LDH / TiO 2 The OCP curve changes of the composite and 304SS under intermittent illumination. 2 The OCP of the composite under illumination is significantly higher than that of TiO 2 Negative, which indicates that ZnAl-LDH / TiO 2 The composite can transfer more electrons to 304SS, protecting the stainless steel from corrosion. When the light is turned off, the potential slowly rises. In the absence of a hole trap, the protective performance of the composite material remains unchanged after three cycles of intermittent light.
[0057] Figure 7 TiO 2 Nanotube arrays and ZnAl-LDH / TiO 2 The IT curve changes of the composite coupled with 304SS under intermittent illumination. When the illumination is turned on, the photocurrent density rapidly shifts positively due to the sudden exposure of the composite to the light, then gradually decays and tends to be stable. After the illumination is turned off, the recombination of the photogenerated carriers causes the photocurrent density to decrease.
[0058] Figure 8 ZnAl-LDH / TiO 2 Long-term OCP changes of the composite coupled with 304SS. When the light is turned on, the OCP drops rapidly to about -350mV, achieving the effect of cathodic protection, and remains stable until the end of the experiment. This shows that ZnAl-LDH / TiO2 The complex has good stability.
[0059] Fig. 9 Optical images of 304SS before (a) and after (b) immersion in 3.5% NaCl solution for 12 h without cathodic protection; 2 In the case of composite photoanode protection, optical images of 304SS before (c) and after (d) immersion in 3.5% NaCl solution for 12 hours. Fig. 9 As shown in a and b, in the absence of cathodic protection, after 304SS was immersed in NaCl solution for 12 hours, obvious pitting corrosion appeared on the surface. Fig. 9 As shown in c and d, 304 stainless steel was treated with ZnAl-LDH / TiO 2 After the composite was cathodically protected for 12 h under continuous illumination, there was no obvious change on the metal surface, indicating that 304SS was well cathodically protected.
[0060] Fig.10 It is TiO 2 Nanotube arrays and ZnAl-LDH / TiO 2 Schematic diagram of the photoelectrochemical cathodic protection mechanism of the composite coupled with 304SS under light conditions. 2 For composite photoanodes, TiO 2 and ZnAl-LDH can generate electrons under light and transfer them to 304SS through an external circuit. 2 Composite TiO 2 The stable structure and advantages of type II heterojunction make TiO 2 The holes in the valence band migrate to the valence band of ZnAl-LDH, effectively improving the separation efficiency of electrons and holes. The photoinduced holes in the valence band are rapidly consumed on the superhydrophilic surface. 2 The conduction band ratio of TiO 2 The conduction band position of NTAs is more negative and can better promote the migration of photoinduced electrons to 304SS.
[0061] The narrow band gap of ZnAl-LDH expands the light absorption range. 2 A type II heterojunction is established between the ZnAl-LDH / TiO 2 It can provide stable cathodic protection for 304SS in NaCl solution for up to 12 hours under light conditions and has good stability.
[0062] The composite photoanode of the present invention is a ZnAl-LDH with a narrow band gap, which improves the absorption capacity of the composite photoanode to visible light and improves the utilization rate of sunlight; ZnAl-LDH and TiO 2 NTAs energy bands match to form a type II heterojunction to improve the efficiency of photogenerated carrier separation; effectively improve the stability of the material, so that it can provide cathodic protection for 304SS for up to 12 hours in a 3.5wt% NaCl solution without a hole trap. It has the advantages of simple synthesis method and high photoelectric conversion efficiency.
[0063] Finally, it should be explained that the specific implementation cases described above are only specific implementation methods of the present invention, but the protection content of the present invention is not limited to the above cases. For those skilled in the art, improvements or replacements made according to the above description should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for preparing a ZnAl-LDH / TiO2 composite photoanode material, characterized in that: TiO2 nanotube arrays were constructed by anodization, and then nanoflower-like ZnAl-LDH was grown on their surface by a hydrothermal method to obtain ZnAl-LDH / TiO2 composite photoanode material.
2. The method for preparing the ZnAl-LDH / TiO2 composite photoanode material according to claim 1, characterized in that: The TiO2 nanotube array was placed in a solution containing Zn(NO3)2·6H2O, Al(NO3)2·9H2O, urea and sodium hydroxide, and nanoflower-like ZnAl-LDH was grown on its surface by a hydrothermal method to obtain a ZnAl-LDH / TiO2 composite photoanode material.
3. The method for preparing the ZnAl-LDH / TiO2 composite photoanode material according to claim 2, characterized in that: The solution containing Zn(NO3)2·6H2O, Al(NO3)2·9H2O and urea contains 0.0675 mol Zn(NO3)2·6H2O, 0.0225 mol Al(NO3)2·9H2O and 0.28 mol urea per liter of water.
4. The method for preparing the ZnAl-LDH / TiO2 composite photoanode material according to claim 2, characterized in that: The hydrothermal reaction temperature is 120° C., and the reaction time is 8 h. After the hydrothermal reaction, the material is dried at 60° C. for 12 h to obtain the material.
5. The method for preparing the ZnAl-LDH / TiO2 composite photoanode material according to claim 1, characterized in that: The TiO2 nanotube array is prepared by anodizing a pretreated titanium foil to obtain a titanium sheet with a TiO2 nanotube array on the surface, and then the titanium sheet is annealed in a muffle furnace and then taken out for use.
6. The method for preparing the ZnAl-LDH / TiO2 composite photoanode material according to claim 5, characterized in that: The anodic oxidation was carried out in an electrolyte with a constant DC voltage of 20 V and an oxidation time of 1.5 h at 5 °C min in air. -1 The heating rate was annealed at 450 °C for 2 h.
7. The method for preparing the ZnAl-LDH / TiO2 composite photoanode material according to claim 5 or 6, characterized in that: The electrolyte is prepared by adding 5.0 g of ammonium fluoride per liter of solution, wherein the solvent is a mixture of ethylene glycol and water in a volume ratio of 10:
1.
8. A ZnAl-LDH / TiO2 composite photoanode material prepared by the method of claim 1, characterized in that: The ZnAl-LDH / TiO2 composite photoanode material with regular nano-flower-like structures uniformly distributed on the surface of the nano-tube array is prepared according to the method of claim 1.
9. An application of the ZnAl-LDH / TiO2 composite photoanode material according to claim 8, characterized in that: The ZnAl-LDH / TiO2 composite photoanode material is used as a photoanode in photoelectrochemical cathode protection.
10. The use of the ZnAl-LDH / TiO2 composite photoanode material according to claim 9, characterized in that: The ZnAl-LDH / TiO2 composite photoanode material is used in suppressing metal corrosion in photoelectrochemical cathode protection.